The psychology of juries - Kovera, Margaret Bull (American Psychological Association, 2017)
Integrating individual and group models of juror decision making / Lora M. Levett and Dennis Devine -- The effects of collaborative remembering on trial verdicts / William Hirst and Charles B. Stone -- Integrating concepts of trial advocacy into juror decision making research / Christina A. Studebaker -- Studying the effects of race, ethnicity, and culture on jury behavior / Jennifer S. Hunt -- Juries compared to what? The need for a baseline and attention to real-world complexity / Jennifer K. Robbennolt and Theodore Eisenberg -- Global juries : a plan for research / Valerie P. Hans, Hiroshi Fukurai, Sanja Kutnjak Ivkovic, and Jaihyun Park -- Jury simulation goals / Jonathan J. Koehler and John B. Meixner, Jr. -- Managing different aspects of validity in trial simulation research / Daniel A. Krauss and Joel D. Lieberman -- Jury simulation research : pros, cons, trends, and alternatives / Brian H. Bornstein -- How typical is Lockhart v. McCree? Ecological validity concerns in court opinions / Mary R. Rose -- Suggested do's and don'ts for future jury research : a swan song / Norbert L. Kerr